Smart DB Monitoring - Ansar, Mohammad Al Sardiaan Syah; Ishak, Maizul (Progress in Engineering Application and Technology, 2021)
Technology has become an important aspect in the current modern world. The existence of it keeps evolving into various applications and machineries that help to reduce the burden on any work in daily life. The key to this rapid advancement is the electrical energy that become the thing that powered up all these technologies. However, users have become careless and neglecting the importance to save this energy that they often wasting it. Electrical appliances at a household were keep switched ON even though it is unused and not monitored resulting in energy waste. This issue can be solved by the presence of IoT (Internet of Things) technologies that can do things wirelessly with the presence of an Internet and smartphone. The development of IoT has introduces a various smart system and one of it is the ability to monitor the power consumption at home from the smartphone or any built website. This project aims to monitor the current from different MCB. By using ESP32 with Blynk application interface. The user can monitor at the same time control their home appliance by using smartphone through internet. The system consist various type of sensor as input. Current transformer and voltage sensor were used this will help the user monitor their power usage at home.